Histological and histochemical Research methods as criteria for Evaluation of anthelmintic Effects on the trematode Organs and tissues - O. I. Bibik; I. A. Arkhipov (Российский паразитологический журнал, 2020)
The purpose of the research is evaluating histological and histochemical research methods as information criteria in identifying the effect of chemicals on trematodes. Materials and methods. The study material was trematodes Fasciola hepatica, F. gigantica, Paramphistomum cervi and Dicrocoelium lanceatum collected during dissecting spontaneously infected animals after they had been treated with anthelmintics (Triclabendazole, Dimezole, Polytrem, Antitrem, Tetraxichol, Tegalid and Fascocid) using various therapeutic doses with appropriate regimens. Trematodes from untreated animals were used as control. The detected material was processed under the generally accepted histological procedure and embedded in paraffin. Microslides, namely, slices of 5–7 µm thick, were stained using histological and histochemical methods and studied under a light microscope. Results and discussion. Morphologically, when the microstructure of organs and tissues of trematodes F. hepatica, F. gigantica, P. cervi and D. lanceatum treated with anthelmintics (Triclabendazole, Dimezole, Polytrem, Antitrem, Tetraxichol, Tegalid and Fascocid) was studied, edema, vacuoles, lysis of tissue and cell structures, and severe basophilia were observed in their body. Protein metabolism imbalance and distorted protein synthesis were recorded histochemically. As an outcome of pathophysiological processes after anthelmintic treatment, necrobiosis detected in trematodes and the developing severe edema lead to colliquative necrosis caused by irreversible dystrophic processes occurred at the level of water and protein metabolism imbalance. Misdirected histochemical reaction of trematodes’ tissues and organs when stained for proteins marks nuclear degeneration, termination of protein molecule synthesis, and protein metabolism failure.